Manuale sulla protezione e circolazione dei dati personali (Firenze University Press, USiena Press, 2026)
This handbook is intended to provide students, practitioners and, more generally, anyone wishing to approach the subject with a tool to acquire a consistent knowledge of the notions and legal concepts relating to the protection and flow of personal data. The analysis of the laws, not limited to the General Data Protection Regulation (EU Reg. 2016/679) and also extended to some aspects of the most recent legal acts, such as the Data Act (EU Reg. 2023/2854) and the Data Governance Act (EU Reg. 2022/868), is enriched by an examination of the most relevant European and national case law, which is essential to understand the rationes and the actual scope of the rules that shape the current law.